Первое обнаружение цестод Tetrabothrius curilensis (Tetraphyllidea) у кашалотов (Physeter catodon L.), добытых в водах Антарктики - Скрябин, А.С.; Муравьева, С.И. (Вестник зоологии, 1972)
Rediscription is given of Tetrabothrius curilensis Gubanov in Delamure, 1955 on the basis of numerous data on Physeter catodon L. caught in the Antarctic waters.
A primary description incomplete and without drawings was made by the samples from
Physeter catodon L., caught in the region of the Kuril Islands.